Alternative strategies to improve success rate of mitral isthmus block - Lee, Ji Hyun (Medicine (Baltimore), 2018)
Achieving bidirectional conduction block (BDB) across the mitral isthmus (MI) is technically challenging. We describe our experience using different ablation strategies for achieving successful MI block. We reviewed the records of patients who had undergone MI ablation for peri-mitral (PM) flutter at our institution from January 2010 to May 2015. We investigated ablation strategies for achieving MI block and their long-term outcomes in terms of recurrence of atrial tachyarrhythmia. Single endocardial MI ablation with or without distal coronary sinus (CS) ablation achieved MI block in 129 out of 236 (54.7%) patients. After failure of MI block, a new MI line ablation, ablation targeting the vein of Marshall (VOM), or anterior line ablation was performed in selected patients. The MI block was achieved in 13 (52.0%) out of 25 patients with new MI line ablation and in 13 (68.4%) out of 19 patients with VOM ablation. Anterior line ablation was tried in 23 patients and the line of block was achieved in 12 (52.2%) patients. Finally, overall PM BDB (PMB, MI block or anterior line block) was achieved in 167 (70.8%) of 236 patients. The incidence atrial tachyarrhythmia was similar between the patients with successful PMB and those with failed PMB (32.9% vs 42.0%, P = .18). In multivariable Cox regression analysis, the PMB was not associated with recurrence of atrial tachyarrhythmia (hazard ratio [HR]: 0.70, 95% confidence interval [CI]: 0.43–1.12). In conclusion, single endocardial MI line with or without distal CS ablation showed limited success for achieving MI block. Additional substrate modifications such as a new MI line ablation, anterior line ablation, or ablation targeting the VOM may improve the success rate of PMB block. However, the benefits of PMB were not clear in this study.